ANALYSIS OF GOVERNMENT POLICY ALIGNMENT ON ADOLESCENTS’ NON-COMMUNICABLE DISEASES PREVENTION AND MANAGEMENT IN SEMARANG CITY - Hendratman, Bevan Pramudito; Alfirdaus, Laila Kholid; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2024)
Non-communicable diseases (NCDs) pose a significant health threat in Indonesia, impacting productive age groups, including adolescents. This underscores the urgent need for heightened awareness and interventions to address unhealthy behaviors and ensure adolescent health and productivity. The research method used is policy analysis study by collecting data through interviews with the Semarang City Health Office, Semarang City Children's Forum, Semarang City Regional Development Planning Agency, Semarang City Adolescents, and analysis of related policy documents. Findings reveal proactive steps by the Semarang City Health Office, including health campaigns and education sessions for adolescents. While the government demonstrates capability in NCD management, challenges such as limited collaboration and incomplete data persist. These findings highlight the importance of enhanced collaboration, program evaluation, budget allocation, and communication strategies for effective NCD prevention and management. The study also acknowledges limitations, including incomplete data and stakeholder engagement challenges, which should be considered in future research and policy development